The impact of a trend pattern for sustainable marketing budgets on turnover dynamics (a case study) - Alexandru Capatina; Adrian Micu; Nicoleta Cristache; Angela Eliza (Contemporary Economics, 2017)
In business practice, sustainable marketing seeks to meet environmental and social sustainability needs. Sustainable marketing budgets should create a balance between market needs and the need to use existing resources as rationally as possible. By recognizing that certain internal and external factors may cause fluctuations in sustainable marketing budgets and have a direct impact on the expected turnover, managers could capture opportunities to channel these budgets into business areas with higher return on investment (ROI). This study highlights the trends of sustainable marketing budgets in the case of one company and assesses their impact on its business turnover. Based on the assumed objective, this study provides explanations regarding the efficiency of sustainable marketing budgets in terms of benefits and, more precisely, on turnover dynamics. From the methodological perspective, the use of the coefficient of variation method allows the assessment of the longitudinal data homogeneity, reflecting the dynamics of the indicators, sustainable marketing budgets and turnovers. The results reveal that monthly sustainable marketing budgets have a significant impact on monthly turnover dynamics, considering the quadratic trend in the case of monthly sustainable marketing budgets and the exponential trend of monthly turnovers. From a managerial perspective, the implications of this study reveal that the more you invest in sustainable marketing, the more revenue your company could earn.
Keywords: M31; M21; O21; O32; 330; sustainable marketing; sustainable development; trend pattern; coefficient of variation